2009
DOI: 10.1038/ng.449
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association of IL28B with response to pegylated interferon-α and ribavirin therapy for chronic hepatitis C

Abstract: The recommended treatment for patients with chronic hepatitis C, pegylated interferon-alpha (PEG-IFN-alpha) plus ribavirin (RBV), does not provide sustained virologic response (SVR) in all patients. We report a genome-wide association study (GWAS) to null virological response (NVR) in the treatment of patients with hepatitis C virus (HCV) genotype 1 within a Japanese population. We found two SNPs near the gene IL28B on chromosome 19 to be strongly associated with NVR (rs12980275, P = 1.93 x 10(-13), and rs8099… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

112
1,888
17
38

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 2,026 publications
(2,055 citation statements)
references
References 22 publications
112
1,888
17
38
Order By: Relevance
“…Genetic and functional studies have identified key molecules and processes involved in clearing HCV spontaneously and using interferon (IFN)‐α based therapies 3, 4, 5, 6, 7, 8, 9. These studies have implicated both innate and adaptive mechanisms in clearing HCV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and functional studies have identified key molecules and processes involved in clearing HCV spontaneously and using interferon (IFN)‐α based therapies 3, 4, 5, 6, 7, 8, 9. These studies have implicated both innate and adaptive mechanisms in clearing HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most impressive findings from Gene Wide Association Studies (GWAS) to date has been the identification of single nuclear polymorphisms (SNPs) upstream of IFN‐λ3 which are protective against HCV chronicity and treatment failure 3, 4, 5, 6, 7. This has been fine mapped to the TT/‐G polymorphism at rs67272382 in a CpG island, which is in strong linkage disequilibrium with IFN‐λ3 and is most likely to be the causal variant, with the possibility of defining a new type 3 IFN, IFN‐λ4 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The three genes encode IFN-k1 (IL29), IFN-k2 (IL28A), and IFN-k3 (IL28B). The same set of SNPs was subsequently associated with natural clearance of HCV.…”
mentioning
confidence: 99%
“…Genome-wide association studies have recently identified genetic variations near the IL28B gene, encoding for interferon (IFN)-k3, as a strong predictor of spontaneous and treatment-induced clearance of hepatitis C infection [13][14][15][16][17][18]. Protective variants at the rs12979860 and rs8099917 loci have consistently been associated with faster decline in viral load and an approximately twofold higher sustained virologic response rate during standard of care treatment, particularly, in patients affected by the difficult to cure HCV genotypes 1 and 4 [19,20].…”
mentioning
confidence: 99%
“…Protective variants at the rs12979860 and rs8099917 loci have consistently been associated with faster decline in viral load and an approximately twofold higher sustained virologic response rate during standard of care treatment, particularly, in patients affected by the difficult to cure HCV genotypes 1 and 4 [19,20]. The mechanism by which these genetic variants influence the outcome of HCV infection, i.e., whether they influence IFN-k3 expression by affecting gene transcription or are linked to a coding variant (Lys70Arg) of the IFN-k3 protein, is still debated [14,18]. However, it is known that these variants result in a different pattern of activation of the innate immune system against HCV infection, as determined by the different basal and IFN-a induced expression of interferon-stimulated genes and inflammatory activity [21,22].…”
mentioning
confidence: 99%